(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2022)
Dear LAJSBA readers, this editorial note has the intention to updateyou with the news from our journal. In this sense, we want to tell you that our editorial team has been renewedwith the incorporation of two Associate Editors, José I. Cuitiño(CONICET, Argentina) and Giorgio Basilici (UNICAMP, Brazil). We want to express deeply thanks to RenataNetto and Fernando Gómez for the excellent work doneduring the last four years.We also express our gratitude to the Board of the Asociación Argentina de Sedimentología for trusting us for this importantand committed task. The journal, since its foundation in 2005 (coming from the AAS Revista since 1994), has been progressively improving its quality and its visibility within the scientific community. LAJSBA is an entirelyonlinefree-access journal witha highlevel scientific quality and designwhich is recognized bythe Latin American Earth Sciences community. In terms of bibliographic indexes, LAJSBA is included in the ranks of SCOPUS, Scimago, Latindex, DOAJ, GeoRef,andSciELO. Some important news can be highlighted from the last two years.Firstly, we want to communicate a great improvement for our journal: the launch of the new LAJSBA website!This website (https://lajsba.sedimentologia.org.ar/index.php/lajsba) represents a great advance for the journal and concentrate not only thesubmission and review systems, but also the repository ofthe complete collection of LAJSBA.This achievement was possible thanks to the support of the members of the AsociaciónArgentina de Sedimentología and we are proud to share it with the entire Latin Americangeoscientist community and from every corner of the world where LAJSBA has a reader. The second essential notice is that, since the volume 26.2 (December 2019) the journal is on regular time! This was possible through the efforts of authors, reviewers and editors, which hardly worked during the last four years. One benefit of the present onlinepublication system is the possibility to manage several volumes in progress in our online platform;this meansthat after the paper acceptance, it will be automatically published as part of future volumes, reducing considerably the time for online publication. Finally, a great news for our sedimentological community is related tothe latestmodification from Scimago Journal Ranking, whichrankedthe journal in the 2nd Quartile in all the categories where it is included (Geology, Paleontology, and Stratigraphy). This was the result of the high visibility gain for LAJSBA which could be interpreted from the statistics in the Scimago web page, where our journal reached in 2021 the record of cites in the last 15 years! We are convinced that maintaining the path marked by previous editorial teams, together with the recent improvements of bibliographic indexes andan active international diffusion,LAJSBAwill increasingly become an attractive journalfor the communication of scientific advances of the Sedimentology and Basin Analysisscientific community.To conclude, we want to emphasize that the future of LAJSBA depends uponthe support of the Latin American sedimentological community, including readers, authors, reviewers, and editors, not just to maintain its importance in our region, but to cross our borders.We repeat once again the message to our readers; we are looking forward to receiving your contributions!